Precarious Work and Legal Protection: Insights into the Implementation of Labor Standards - Yeti Kurniati; Wiwit Julianasari (Khazanah Hukum, 2026)
The development of industrial relations in Indonesia demonstrates a structural shift toward the dominance of informal and precarious employment, characterized by fixed-term employment contracts (Perjanjian Kerja Waktu Tertentu/PKWT) and outsourcing arrangements that often weaken legal protection and social security coverage. This study examines the gap between normative labor regulations and the practical implementation of legal protection for precarious workers in Indonesia. Rather than employing an empirical field-based method, the research adopts a qualitative socio-legal doctrinal approach, analyzing primary legal materials, including Law No. 13 of 2003 on Manpower, Law No. 11 of 2020 on Job Creation and its implementing regulations, Constitutional Court decisions, and relevant ministerial regulations as well as secondary legal literature and policy documents. The unit of analysis focuses on the regulation and governance of fixed-term contracts and outsourcing arrangements in the post–Job Creation reform period. The findings reveal three central themes. First, regulatory reforms aimed at increasing labor market flexibility have expanded the scope of fixed-term and outsourced work, thereby intensifying employment insecurity and blurring employment status. Second, although labor standards are formally regulated, substantive protection remains limited due to ambiguities in employment classification and weak enforcement mechanisms. Third, institutional constraints in labor inspection and dispute resolution mechanisms contribute to a predominantly reactive and fragmented enforcement pattern. These dynamics reflect structurally unequal industrial relations, where workers’ bargaining power remains limited and access to effective remedies is uneven. The study concludes that legal protection for precarious workers in Indonesia remains structurally constrained despite formal regulatory guarantees. To enhance effectiveness, the paper recommends strengthening labor inspection institutions, clarifying the legal boundaries of fixed-term and outsourcing arrangements, expanding access to legal aid and collective representation, and rebalancing labor policy to ensure that flexibility does not undermine fundamental labor rights.